AuAg-CeO2 nanocage and application thereof in detection of ALP

AuAg@CeO2 nanocage was prepared by a two-step hydrothermal method and enhanced its activity using near-infrared laser, a colorimetric method for ALP detection was constructed, which solved the problems of low sensitivity and complex operation of traditional detection methods, and achieved high sensitivity and fast ALP detection.

CN119608159APending Publication Date: 2025-03-14金凤实验室
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411692303.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Traditional ALP detection methods have problems such as complex operation, low sensitivity, large interference and limited sample types, making it difficult to achieve early diagnosis of low cost, simple operation and non-invasiveness.

Method used

AuAg@CeO2 nanocage was prepared by two-step hydrothermal method, and its peroxidase-like activity was enhanced by near-infrared laser irradiation, and a colorimetric detection method was constructed for detecting ALP.

Benefits of technology

It realizes high sensitivity ALP detection, which is simple and fast, and can detect ALP content in real time, with potential early diagnosis applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608159A_ABST
    Figure CN119608159A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of chemical detection, and particularly relates to an AuAg-coated CeO2 nanocage and application thereof in detection of ALP. According to the invention, the AuAg-coated CeO2 nanocage with a hollow structure is prepared by adopting a two-step hydrothermal method, and the nanomaterial has good photo-thermal performance. Based on the photo-thermal enhanced peroxidase activity property of the AuAg-coated CeO2 nanocage, the POD activity is regulated and controlled by near-infrared photothermal, an ALP colorimetric detection method is further constructed, ALP content determination is converted into a color signal, and the color signal is read by an intelligent machine. The method is simple, rapid and sensitive, can be used for detecting the ALP content in real time, and has important significance on early diagnosis of diseases such as liver and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical detection, and particularly relates to an AuAg@CeO2 nano cage and an application thereof in detecting ALP. Background Art

[0002] Alkaline phosphatase (ALP) is an enzyme widely distributed in organisms. It plays a vital role in the dephosphorylation of nucleic acids, proteins and other biomolecules. Abnormal expression of ALP is closely related to many diseases and has been considered a potential target for a variety of diseases. Its level is associated with liver, prostate, bone tissue and endocrine system diseases. Therefore, the specific detection of ALP can help evaluate certain related physiological and pathological states, and rapid disease detection is the key to predicting outcomes and effectively managing diseases. However, traditional detection strategies have many defects: reliance on expensive instruments, complex operating procedures, low sensitivity, large interference, and limited target sample types. Therefore, it is urgent to develop a low-cost, simple-to-operate, non-invasive early diagnosis method for ALP to replace direct measurement of blood or tissue samples.

[0003] Nanozymes are a class of nanomaterials with catalytic properties. Compared with natural enzymes, they are easy to store, low-cost and not easy to inactivate. Since the discovery of magnetic Fe3O4 nanoparticles with intrinsic horseradish peroxidase activity in 2007, a large number of nanomaterials with excellent enzyme-like activity have been reported in the past decade. A variety of sensing methods have been developed using the specific color reaction of nanozymes with substrates, which have been fully applied in various fields such as anti-oxidation, immunoassays and environmental monitoring. However, as a promising alternative to natural enzymes, despite a large number of research results, the unsatisfactory simulated enzyme activity still limits its application. Therefore, improving the catalytic performance of nanozymes has become the key for scientists to solve this problem.

[0004] Among the numerous nanomaterials, plasmonic nanostructures can capture light in a wide spectrum and convert light energy into heat energy, thereby increasing the temperature and enhancing the catalytic performance of nanozymes through photothermal enhancement. It is reported that localized surface plasmon resonance (LSPR) can decay through radiation pathways, produce local heating and field enhancement near the particles, and can also generate hot electrons and holes through non-radiative means. Therefore, LSPR provides a new way to further improve the catalytic activity of nanozymes.

[0005] In the prior art, patent CN117772195A discloses a method for preparing a AuAg-CeO2 bimetallic supported photocatalyst. The patent synthesizes CeO2 nanomaterials rich in oxygen vacancies based on hydrothermal reaction and plasma gas treatment method; then prepares AuAg-CeO2 bimetallic supported photocatalyst based on the CeO2 nanomaterials rich in oxygen vacancies, and further applies it to photocatalytic carbon dioxide reduction. Summary of the invention

[0006] In view of this, the present invention proposes an AuAg@CeO2 nanocage with good photothermal properties and a preparation method thereof, and at the same time constructs a colorimetric detection method for detecting ALP based on the photothermal properties of the nanomaterial.

[0007] One of the purposes of the present invention is to provide a method for preparing AuAg@CeO2 nanocages using a two-step hydrothermal method.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] The method for preparing AuAg@CeO2 nanocages by a two-step hydrothermal method comprises the following steps:

[0010] (1) HAuCl4, CTAB, and NaBH4 solutions are sequentially mixed to obtain reaction solution A;

[0011] (2) mixing HAuCl4, CTAC, and ascorbic acid solution in sequence to obtain reaction solution B;

[0012] (3) adding the reaction solution A obtained in step (1) to the reaction solution B obtained in step (2) to obtain a quasi-spherical Au nanoseed dispersion;

[0013] (4) mixing DTAC, AA, AgNO3 and the Au nanoseed dispersion obtained in step (3), and reacting in a water bath to obtain Au@Ag core-shell nanocubes;

[0014] (5) adding HAuCl4 solution to the Au@Ag core-shell nanocubes obtained in step (4) to continue the reaction to obtain a AuAg nanocage dispersion;

[0015] (6) Add CTAB and K2PtCl6 to the AuAg nanocage dispersion obtained in step (5) in sequence and vortex; then add Ce(AC)3 and react to obtain AuAg@CeO2 nanocage dispersion.

[0016] Further, in step (1), the volume ratio of the HAuCl4, the CTAB, and the NaBH4 solution is 4-6:4-6:0.5-0.7; and / or in step (2), the volume ratio of the HAuCl4, the CTAC, and the ascorbic acid solution is 3-5:3-5:2-4; and / or in step (3), the volume ratio of the reaction solution A to the reaction solution B is 0.04-0.06:8-15; and / or in step (4), the volume ratio of the DTAC, the AA, the Ag The volume ratio of NO3 and the Au nanoseed dispersion is 2-5:0.4-0.6:0.4-0.6:0.01-0.03; and / or in step (5), the volume ratio of the Au@Ag core-shell nanocubes and the HAuCl4 solution is 3.5-4.5:1-2; and / or in step (6), the volume ratio of the AuAg nanocage dispersion, the CTAB, the K2PtCl6, and the Ce(AC)3 is 15-20:15-20:4-10:4-10.

[0017] Preferably, in step (1), the volume ratio of the HAuCl4, the CTAB and the NaBH4 solution is 5:5:0.6; the concentration of the HAuCl4 is 0.5 mM; the concentration of the CTAB is 200 mM; and the concentration of the NaBH4 solution is 10 mM.

[0018] Preferably, in step (1), the reaction condition is to stand for 8 to 20 minutes, most preferably for 10 minutes.

[0019] Preferably, in step (2), the volume ratio of the HAuCl4, the CTAC and the ascorbic acid solution is 4:4:3; the concentration of the HAuCl4 is 0.5 mM; the concentration of the CTAC is 200 mM; and the concentration of the ascorbic acid solution is 100 mM.

[0020] Preferably, in step (3), the volume ratio of the reaction solution A to the reaction solution B is 0.05:11.

[0021] Preferably, in step (3), the reaction condition is to stand for 25 to 60 minutes, most preferably for 30 minutes.

[0022] Preferably, after the reaction in step (3) is completed, the reaction solution is centrifuged at 15,000 rpm for 60 min, the supernatant is discarded and the mixture is washed once with deionized water, and water is added to the original volume to obtain a quasi-spherical Au nanoseed dispersion.

[0023] Preferably, in step (4), the volume ratio of the DTAC, the AA, the AgNO3 and the Au nanoseed dispersion is 3:0.5:0.5:0.02; the concentration of the DTAC is 20 mM; the concentration of the AA is 10 mM; and the concentration of the AgNO3 is 2 mM.

[0024] Furthermore, in step (4), the reaction conditions are 80-100° C. in a water bath for 5-10 h, more preferably 90° C. in a water bath for 6 h.

[0025] Preferably, in step (5), the volume ratio of the Au@Ag core-shell nanocubes to the HAuCl4 solution is 4.02:1.25; and the concentration of the HAuCl4 solution is 0.5 mM.

[0026] Preferably, in step (5), the reaction time is 1 h.

[0027] Preferably, after the reaction in step (5) is completed, the reaction solution is centrifuged at 10,000 rpm for 10 min, the supernatant is discarded and the mixture is washed once with deionized water, and the mixture is filled to 10 mL to obtain an AuAg nanocage dispersion.

[0028] Preferably, in step (6), the volume ratio of the AuAg nanocage dispersion, the CTAB, the K2PtCl6, and the Ce(AC)3 is 10:10:5:5; the concentration of the CTAB is 0.5 mM; the concentration of the K2PtCl6 is 0.5 mM; and the concentration of the Ce(AC)3 is 10 mM.

[0029] Preferably, in step (6), the vortex time is 5 min;

[0030] Furthermore, in step (6), the reaction conditions are 90-120° C. for 50 min-2 h, more preferably 100° C. for 1 h.

[0031] Preferably, after the reaction in step (6) is completed, the obtained reaction solution is centrifuged at 8000 rpm for 10 min, the supernatant is discarded and washed twice with deionized water, and the water is replenished to 10 mL to obtain an AuAg@CeO2 nanocage dispersion.

[0032] The second object of the present invention is to provide an AuAg@CeO2 nanocage prepared by the above method.

[0033] To achieve the above object, the present invention adopts the following technical solutions:

[0034] AuAg@CeO2 nanocages prepared using the aforementioned method.

[0035] Furthermore, the AuAg@CeO2 nanocage has a hollow structure.

[0036] Furthermore, the peroxidase-like (POD) activity of the AuAg@CeO2 nanocage can be enhanced by near-infrared laser irradiation.

[0037] The present invention adopts a three-dimensional nanocage structure that is easy to adjust its LSPR properties and has a higher photothermal conversion efficiency, and combines it with a nanomaterial with strong nanozyme activity to form a heterojunction, and greatly improves the catalytic activity of the nanozyme by enhancing the photothermal performance through plasmon. The AuAg@CeO2 nanocage prepared by the present invention has good photothermal performance. The electron transfer between the AuAg alloy and CeO2 is promoted by near-infrared laser irradiation, thereby effectively enhancing its peroxidase-like activity. In the presence of H2O2, it can effectively catalyze TMB oxidation to become blue. ALP is added in the presence of L-ascorbic acid-2-phosphate (AAP). Since ALP can effectively react with AAP to generate ascorbic acid (AA), its POD activity is effectively inhibited, and the color of the system becomes lighter.

[0038] The third object of the present invention is to provide a method for detecting ALP content using the aforementioned AuAg@CeO2 nanocage.

[0039] To achieve the above object, the present invention adopts the following technical solutions:

[0040] The method for detecting the ALP content using the aforementioned AuAg@CeO2 nanocage comprises the following steps:

[0041] A. preparing a reaction solution for incubating ALP: mixing Tris-HCl, L-ascorbic acid-2-phosphonate, ALP and deionized water, and reacting to obtain a reaction solution 1;

[0042] B. Take different volumes of the reaction solution 1, mix with the AuAg@CeO2 nanocage dispersion, HAc-NaAc buffer solution, TMB solution, H2O2 and ionized water to obtain a series of standard working solutions; irradiate the series of standard working solutions under laser, and then use UV-visible-near infrared spectrometer to test its absorption intensity at 400-800nm; and use ΔA 652 The vertical axis is the ordinate, the concentration of ALP is the horizontal axis, and the standard working curve is established;

[0043] C. By using RGB color picking, with R, G, B values ​​as the ordinate and ALP concentration as the abscissa, a colorimetric analysis method for detecting ALP was established to obtain a standard working curve for colorimetric detection of ALP;

[0044] D. Detect the RGB value of the sample to be tested, substitute it into the standard working curve obtained in step C, and obtain the ALP concentration of the sample to be tested.

[0045] Preferably, in step A, the volume ratio of the Tris-HCl, the L-ascorbic acid-2-phosphonate, the ALP and the deionized water is 9-11:0.8-1.2:0.8-1.2:10-15, preferably 10:1:1:13.

[0046] Preferably, in step A, the total volume of the reaction system is 1.5 mL.

[0047] Preferably, in step A, the pH of the Tris-HCl is 7.0 to 9.0, most preferably 8.0.

[0048] Preferably, in step A, the concentration of L-ascorbic acid-2-phosphonate is 10 mM.

[0049] Preferably, in step A, the concentration of ALP is 10 μg / mL.

[0050] Preferably, in step A, the reaction conditions are 35-40° C. water bath reaction for 25-60 min, and most preferably 37° C. water bath reaction for 30 min.

[0051] Further, in step B, the final concentration of ALP in the series of standard working solutions is 0U / L, 0.67U / L, 1.33U / L, 2.00U / L, 2.67U / L, 3.33U / L, 4.00U / L, 4.67U / L, 5.33U / L, 6.00U / L, and 6.67U / L.

[0052] Further, in step B, the linear equation for detecting ALP is ΔA 652 =0.0747c+0.1547, r=0.9949, and the linear range of detection is 0.67U / L-6.67U / L.

[0053] Furthermore, in step B, the final concentration of the AuAg@CeO2 nanocage dispersion is 18-25 μg / mL; the pH of the HAc-NaAc buffer solution is 3.0-4; the final concentration of the TMB solution is 0.9-1.2 mM; and the final concentration of the H2O2 is 6-15 mM.

[0054] Preferably, in step B, the final concentration of the AuAg@CeO2 nanocage dispersion is 20 μg / mL; the pH of the HAc-NaAc buffer solution is 3.5; the final concentration of the TMB solution is 1 mM; and the final concentration of the H2O2 is 10 mM.

[0055] More preferably, in step B, the preparation method of a series of standard working solutions is as follows: add 30 μL of 1 mg / mL AuAg@CeO2 NCs dispersion, 500 μL of pH=3.5 HAc-NaAc buffer solution, 500 μL of 3 mM TMB solution, and 150 μL of 100 mM H2O2, and then add 0 μL, 25 μL, 50 μL, 75 μL, 100 μL, 125 μL, 150 μL, 175 μL, 200 μL, 225 μL, and 250 μL of reaction solution 1, respectively, and then fill up to 1500 μL with deionized water.

[0056] Preferably, in step B, the laser irradiation wavelength is 808 nm and the power density is 1 w / cm 2 , the irradiation time is 10min.

[0057] Further, in step C, the linear equation for colorimetric detection of ALP is ΔV R =10.2304c+27.3758, where ΔV R represents the relative value of R (i.e., the difference between the system R value when the system ALP concentration is 0 and the R value when a certain ALP concentration is added to the system), c represents the ALP concentration, and the linear range of its detection is 1.33-6.67U / L.

[0058] Furthermore, in step D, the pretreated sample to be tested is incubated with AAP at 37°C; then it is added to the detection system containing AuAg@CeO2 NCs-TMB-H2O2 and irradiated with laser. Finally, the sample is photographed and the color is picked up using a mobile phone color picking software to obtain the R value.

[0059] Preferably, the detection system includes: 30 μL AuAg@CeO2NCs dispersion, 500 μL HAc-NaAc buffer solution with pH=3.5, 500 μL TMB solution, 150 μL H2O2, 250 μL sample solution, and finally add deionized water to 1.5 mL. The final concentration of the AuAg@CeO2 nanocage dispersion is 20 μg / mL; the pH of the HAc-NaAc buffer solution is 3.5; the final concentration of the TMB solution is 1 mM; and the final concentration of the H2O2 is 10 mM.

[0060] Preferably, in step D, the laser is irradiated at 808 nm for 10 min at a power density of 1 W / cm 2 The absorbance value of the sample to be tested at 652 nm is tested using an ultraviolet-visible-near infrared spectrometer to obtain its R value.

[0061] Furthermore, the samples to be tested include serum and urine samples.

[0062] Preferably, the sample to be tested is pretreated by centrifugation, dilution (gradual dilution to 1000 times of the original solution), etc.; the centrifugation speed is 15000 rpm and the time is 15 min; the dilution is gradual dilution to 1000 times of the original solution.

[0063] The beneficial effects of the present invention are:

[0064] 1. The present invention successfully prepared AuAg@CeO2 nanocages (AuAg@CeO2NCs) with a hollow structure by a two-step hydrothermal method. The nanomaterial has good photothermal properties, which provides support for the further construction of a highly sensitive ALP colorimetric detection method.

[0065] 2. This invention proposes a new colorimetric analysis method for ALP content based on AuAg@CeO2 NCs sensor. By regulating POD activity by near-infrared photothermal, the colorimetric analysis of ALP is constructed, and the ALP content determination is converted into a color signal, which is read out by an intelligent machine. This method is simple, rapid, and sensitive, and can detect the ALP content in real time.

[0066] 3. The ALP colorimetric detection method proposed in the present invention has been successfully applied to the quantitative detection of ALP in actual samples, and is expected to provide assistance for the early diagnosis of liver diseases and other diseases.

[0067] 4. The ALP colorimetric detection method proposed in the present invention utilizes the plasma properties of AuAg alloy nanostructures, which exhibit good photothermal performance under near-infrared laser irradiation, thereby enhancing its simulated enzyme activity through photothermal enhancement, converting the detection signal into a color signal for readout, thereby amplifying the detection signal and shortening the detection time, thereby realizing rapid and portable detection of ALP. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 The electron microscope test results of AuAg and AuAg@CeO2 nanocages are shown in Figure 2. Figure 1 -A is the SEM image of AuAg nanocage; Figure 1 -B is the TEM image of AuAg nanocage; Figure 1 -C is the SEM image of AuAg@CeO2 nanocage; Figure 1 -D is the TEM image of AuAg@CeO2 nanocage;

[0069] Figure 2 The graph shows the test results of the hydrated particle size of AuAg and AuAg@CeO2 nanocages;

[0070] Figure 3 The HAADF diagram of AuAg@CeO2 nanocage and the corresponding EDS test result diagram, where: Figure 3-A is the HAADF diagram of AuAg@CeO2 nanocage, Figure 3 -B is the combination diagram of Au, Ag, Ce, and O in AuAg@CeO2 nanocage. Figure 3 -C is the distribution diagram of Au element in AuAg@CeO2 nanocage, Figure 3 -D is the distribution diagram of Ag element in AuAg@CeO2 nanocage, Figure 3 -E is the distribution diagram of Ce element in AuAg@CeO2 nanocage, Figure 3 -F is the distribution diagram of O element in AuAg@CeO2 nanocage;

[0071] Figure 4 Absorption spectra of AuAg and AuAg@CeO2 nanocages;

[0072] Figure 5 Schematic diagram of the photothermal experiment device using 808nm laser and near-infrared thermal imager;

[0073] Figure 6 To use different power densities (808nm, 1W / cm 2 ) A graph showing the temperature of a material changing with time when irradiated with laser;

[0074] Figure 7 For (808nm, 1W / cm 2 ) A graph showing the temperature of the system changing with the material concentration during laser irradiation;

[0075] Figure 8 The laser (808nm, 1W / cm 2 ) Thermal imaging images of irradiation 0-10min;

[0076] Fig. 9 The material was lasered on / off 5 times (808nm, 1W / cm 2 ) A diagram showing the heating / cooling of the cycle;

[0077] Fig.10 This is a graph showing the temperature variation over time after the material is irradiated with laser for 15 minutes and then the light source is turned off and cooled;

[0078] Fig.11 This is the calculation result diagram of the material's light-to-heat conversion efficiency;

[0079] Fig.12 The POD test results of AuAg@CeO2 NCs enhanced by photothermal treatment are shown in Figure 2. Fig.12 -A is the absorption spectrum of TMB-H2O2 system under different conditions; Fig.12 -B is the absorption spectrum of ABTS-H2O2 system under different conditions; Fig.12-C is the absorption spectrum of OPD-H2O2 system under different conditions;

[0080] Fig.13 This is a diagram constructed based on the photothermal enhanced AuAg@CeO2 NCs POD colorimetric detection ALP method, in which the embedded figure is the corresponding reaction liquid color photo under different conditions;

[0081] Fig.14 This is a result diagram of the reaction condition optimization experiment in Example 5, wherein: Fig.14 -A is a graph testing the absorption of AuAg@CeO2NCs with different concentrations at 652nm; Fig.14 -B is a graph testing the absorption of AuAg@CeO2NCs at 652nm under different pH conditions; Fig.14 -C is a graph showing the absorption of AuAg@CeO2NCs at 652nm under different TMB concentrations; Fig.14 -D is a graph testing the absorption of AuAg@CeO2NCs at 652nm under different H2O2 concentrations;

[0082] Fig.15 This is the UV absorption spectrum of ALP detected by the system;

[0083] Fig.16 It is the standard working curve diagram for the system to detect ALP;

[0084] Fig.17 This is a photo of the color change of the reaction solution in the presence of ALP at different concentrations;

[0085] Fig.18 It is a graph of RGB color values ​​of the reaction solution color photograph in the presence of different concentrations of ALP;

[0086] Fig.19 This is the standard working curve diagram for colorimetric detection of ALP;

[0087] Fig. 20 This is the result diagram of the system's selectivity and anti-interference ability test for ALP, where: Fig. 20 -A is the selectivity test result diagram, Fig. 20 -B is the anti-interference ability test result diagram. DETAILED DESCRIPTION

[0088] The technical solution of the present invention will be further described clearly and completely in conjunction with specific embodiments below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work belong to the protection scope of the present invention.

[0089] Example 1. Synthesis and characterization of AuAg@CeO2 nanocages (AuAg@CeO2 NCs)

[0090] (1) Synthesis of AuAg@CeO2 nanocages (AuAg@CeO2 NCs)

[0091] 1) Preparation of quasi-spherical Au seeds: 5 mL (0.5 mM) of HAuCl4 and 5 mL (200 mM) of cetyltrimethylammonium bromide (CTAB) solution were added into a 20 mL clean glass bottle in sequence, and then 0.6 mL (10 mM) of freshly prepared NaBH4 solution was quickly injected and mixed thoroughly. The mixture was allowed to stand for 10 min to obtain a brown reaction solution. Take another 20mL clean glass bottle, add 4mL (0.5mM) HAuCl4, 4mL (200mM) hexadecyltrimethylammonium chloride (CTAC) and 3mL (100mM) ascorbic acid (AA) solution in sequence, mix well, wait until the solution becomes colorless, then add 50μL of the above brown reaction solution, mix well and let stand for 30min to obtain a wine-red quasi-spherical Au nanoseed dispersion, centrifuge at 15000rpm for 60min, discard the supernatant and wash once with deionized water, add water to the original volume, and place the product at 4℃ for use.

[0092] 2) Take 3mL (20mM) of docosyltrimethylammonium chloride (DTAC), 0.5mL (10mM) of AA, 0.5mL (2mM) of AgNO3 and 20μL of the Au seed solution prepared above in a 20mL clean glass bottle, mix well, and react in a 90℃ water bath for 6h to obtain orange Au@Ag core-shell nanocubes. Then add 1.25mL (0.5mM) of HAuCl4 solution and continue to react for 1h until the solution turns blue. This is the AuAg nanocage dispersion. The product is centrifuged at 10000rpm for 10min, the supernatant is discarded and washed once with deionized water, the water is replenished to 10mL, and placed at 4℃ for standby use.

[0093] 3) Add 10mL of AuAg nanocage dispersion prepared above to a 50mL centrifuge tube, add 10mL (0.5mM) of hexadecyltrimethylammonium bromide (CTAB), 5mL (0.5mM) of K2PtCl6 and vortex for 5min, then add 5mL (10mM) of Ce(AC)3 and mix well, transfer the above reaction solution to a 100mL reactor, react at 100℃ for 1h, and obtain AuAg@CeO2 nanocage dispersion. Centrifuge the product at 8000rpm for 10min, discard the supernatant and wash twice with deionized water, add water to 10mL, and place at 4℃ for use.

[0094] (2) Characterization of AuAg@CeO2 NCs

[0095] AuAg@CeO2 NCs were characterized by SEM, TEM, DLS and EDS. Figure 1 As shown in A and B, the SEM and TEM results of AuAg NCs show that they are hollow nanocage structures. Figure 1 As shown in C and D, the SEM and TEM results of AuAg@CeO2 NCs show that CeO2 successfully grows on the surface and inside of AuAg NCs, forming a heterojunction structure. This result shows the successful synthesis of AuAg and AuAg@CeO2 nanocages, in which CeO2 mainly grows on the outer surface of the nanocage. The hydrated particle size before and after the growth of CeO2 was tested by DLS, and the results showed that the particle size of AuAg@CeO2 NCs increased significantly, as shown in Figure 2. Figure 2 As shown in Figure 2, after AuAg nanocages grow CeO2 to form AuAg@CeO2 nanocages, their hydrated particle size increases from 78nm to 169nm. In addition, the EDS test results are shown in Figure 2. Figure 3 As shown in the figure, the results fully demonstrate the distribution of Au, Ag, Ce, and O elements. From the element distribution diagram and combination diagram of Au, Ag, Ce, and O, it can be seen that Au and Ag are evenly distributed on the nanocage framework, while CeO2 is distributed on the outer surface of the nanocage and also has a small amount distributed inside its cavity. The above results indicate the successful preparation of AuAg@CeO2 NCs.

[0096] Example 2. Photothermal performance test of AuAg@CeO2 NCs

[0097] (1) Solution preparation

[0098] All solutions in the experimental process were prepared with deionized water as the solvent and were prepared and used immediately.

[0099] (2) AuAg@CeO2 NCs absorption spectrum test

[0100] Take 1mL of the prepared AuAg@CeO2 NCs dispersion in a 5mL centrifuge tube, add deionized water to dilute to 3mL, mix thoroughly, and use a UH4150 UV-Vis-NIR absorption spectrometer to test its absorption wavelength. The slit width is set to 10nm and the scanning speed is 600nm / min. Finally, it is measured that AuAg@CeO2 NCs has strong absorption in the near-infrared region, indicating that it has photothermal conversion ability.

[0101] (3) Photothermal performance and photothermal conversion efficiency test of AuAg@CeO2 NCs

[0102] The photothermal performance of AuAg@CeO2NCs was tested using an 808nm near-infrared laser and a near-infrared thermal imager. First, the distance between the light source and the well plate was adjusted to 5cm so that the light beam hit a small hole in the 48-well plate vertically. Then the laser light source was adjusted to focus so that the light spot just completely covered the small hole. The laser power at this time was measured with a power meter, and the spot area was measured to calculate the power density. Secondly, the near-infrared thermal imager was fixed vertically above the well plate, the near-infrared thermal imager was turned on, and the computer software (AnalyzIR) was connected. The position of the thermal imager and the well plate was constantly adjusted to ensure clear imaging in the working area of ​​the thermal imager. Finally, 1500μL of AuAg@CeO2NCs solution was placed in the well plate irradiated by the laser, the laser was turned on, and a stopwatch was used to time it. The video was recorded in the working area of ​​the computer thermal imager, and the imaging was recorded at intervals of only 20s. The imaging changes of the sample within 10min of laser irradiation were recorded, and the temperature-time (Tt) curve was derived using AnalyzIR.

[0103] The calculation formula of photothermal conversion efficiency (η) is shown in the following formula (1):

[0104]

[0105] Where η is the light-to-heat conversion efficiency, h is the heat transfer coefficient, A is the surface area of ​​the container, and ΔT max Represents the difference between the maximum steady-state temperature of the photothermal agent and room temperature, represents the difference between the maximum steady-state temperature of the solvent (H2O) and room temperature, I is the laser power density, and its calculation formula is shown in formula (2); A ( is the absorbance value of the photothermal agent at the corresponding laser wavelength.

[0106]

[0107] Wherein, W represents power, the unit is W; r is the radius of the laser aperture, the unit is cm.

[0108] Therefore, in equation (1), only hA is unknown. In order to obtain the value of hA, q is introduced and defined as:

[0109]

[0110] Where, ΔT = TT surr (T represents the real-time temperature of the solution during irradiation, T surr represents the ambient temperature, i.e. the initial temperature of the solution), ΔT max =T max -T surr (T max represents the maximum steady-state temperature of the solution during irradiation).

[0111] hA can be calculated by the following formula:

[0112]

[0113] Where τ is the cooling time (t) and the slope of the linear equation -ln(q); m is the mass of the solvent; and Cp is the specific heat capacity of the solvent.

[0114] 1) Temperature change of AuAg@CeO2 NCs dispersion irradiated for 0-10 min under different power densities: 1500 μL of the material dispersion was placed in a 48-well plate, and the power density of the 808-nm laser was adjusted to 0.33 W / cm 2 , 0.50W / cm 2 , 1.00W / cm 2 , use a digital thermometer to record the dispersion temperature from 0 to 10 min.

[0115] 2) Temperature change of AuAg@CeO2 NCs dispersions with different concentrations during irradiation for 0-10 min: 1500 μL of dispersions with concentrations of 10 μg / L, 20 μg / L, 30 μg / L, 40 μg / L, and 50 μg / L were placed in a 48-well plate, and the power density of the 808 nm laser was adjusted to 1.00 W / cm 2 The temperature of the dispersion was recorded with a digital thermometer from 0 to 10 minutes. Deionized water was used as the control group for the test.

[0116] 3) Photothermal stability test of AuAg@CeO2 NCs dispersion: 1500 μL of 40 μg / L material dispersion was placed in a 48-well plate, and the power density of the 808 nm laser was adjusted to 1.00 W / cm 2 The dispersion temperature was tested every 20 seconds using a digital thermometer. The laser was irradiated for 15 minutes, the laser was turned off, and the dispersion was cooled to room temperature. The laser was turned on again, and the test was repeated 5 times to investigate the photothermal stability of the material.

[0117] 4) AuAg@CeO2 NCs photothermal conversion efficiency test: Take 1500μL of 50μg / L material dispersion into a 48-well plate, and adjust the 808nm laser power density to 1.00W / cm 2 , use a digital thermometer to test the dispersion temperature every 20 seconds. Laser irradiation for 15 minutes, turn off the laser, and wait for it to cool to room temperature. Use deionized water as a blank control and repeat the experiment. And use the above formula to calculate its photothermal conversion efficiency.

[0118] The photothermal performance test results of AuAg@CeO2 NCs are shown in Figures 4 to 11The data show that the nanomaterial has good photothermal performance. As the laser power density increases, its temperature rises more, and its temperature rise depends on the material concentration. After 5 cycles, the temperature of the material can still rise to above 50°C under irradiation, indicating that the material has good photothermal stability. Further testing and calculation of the material's photothermal conversion efficiency can reach 54.0%.

[0119] Example 3. AuAg@CeO2 NCs POD activity test

[0120] The POD enzyme activity of the material was investigated using 3,3',5,5'-tetramethylbenzidine (TMB), o-phenylenediamine (OPD) and 2,2-azino-bis(3-ethyl-benzothiazole-6-sulfonic acid) diammonium salt (ABTS) as chromogenic substrates.

[0121] Control group 1: 500 μL of HAc-NaAc buffer solution with pH = 3.5, 500 μL (3 mM) of TMB solution, 150 μL (100 mM) of H2O2 were added to a 2 mL centrifuge tube in sequence, and finally deionized water was added to 1500 μL.

[0122] Control group 2: 500 μL of HAc-NaAc buffer solution with pH = 3.5, 500 μL (3 mM) of TMB solution, 150 μL (100 mM) of H2O2 were added to a 2 mL centrifuge tube in sequence, and finally deionized water was added to 1500 μL.

[0123] Control group 3: 30 μL (1 mg / mL) of AuAg@CeO2 NCs dispersion, 500 μL of HAc-NaAc buffer solution with a pH of 3.5, 500 μL (3 mM) of TMB solution, and 150 μL (100 mM) of H2O2 were added to a 2 mL centrifuge tube in sequence, and finally deionized water was added to 1500 μL.

[0124] Experimental group: 30 μL (1 mg / mL) of AuAg@CeO2 NCs dispersion, 500 μL of HAc-NaAc buffer solution with a pH of 3.5, 500 μL (3 mM) of TMB solution, and 150 μL (100 mM) of H2O2 were added to a 2 mL centrifuge tube in sequence, and finally deionized water was added to make up to 1500 μL.

[0125] The above samples were mixed thoroughly, and the control group 1 and the control group 3 were allowed to react at room temperature for 10 min. The control group 2 and the experimental group were exposed to 808 nm laser (1 w / cm 2) for 10 min, and then the absorption spectra of 400-800 nm were measured respectively. The same method was used with ABTS and OPD as substrates, except that the initial concentration of ABTS solution was changed to 6 mM, the test wavelength range was 375-500 nm, and the initial concentration of OPD was changed to 12 mM, and the test wavelength range was 300-600 nm.

[0126] The POD test results of AuAg@CeO2 NCs are shown in Fig.12 As shown. Using the typical TMB-H2O2 as the chromogenic substrate, under near-infrared laser irradiation, the characteristic absorption peak of TMB (652nm) was greatly enhanced compared with the control group; similar experimental results were obtained when ABTS or OPD were used as the chromogenic substrate. Therefore, due to the photothermal properties of the material, the peroxidase-like activity of AuAg@CeO2NCs can be significantly enhanced under near-infrared laser irradiation.

[0127] Example 4. Construction of a colorimetric ALP detection method based on photothermal enhanced AuAg@CeO2 NCs POD

[0128] Preparation of reaction solution for incubating ALP: 6000 μL Tris-HCl (pH=8.0), 600 μL (10 mM) L-ascorbic acid-2-phosphate (AAP), 600 μL (10 μg / mL) ALP, and 7800 μL deionized water were respectively placed in a 15 mL centrifuge tube, mixed thoroughly, and placed in a 37°C water bath for reaction for 30 min. This was recorded as reaction solution 1.

[0129] Sample 1: In a 2 mL centrifuge tube, add 30 μL (1 mg / mL) of AuAg@CeO2NCs dispersion, 500 μL of HAc-NaAc buffer solution with a pH of 3.5, 500 μL (3 mM) of TMB solution, and 150 μL (100 mM) of H2O2 in sequence, and finally fill with deionized water to 1500 μL.

[0130] Sample 2: In a 2 mL centrifuge tube, add 30 μL (1 mg / mL) of AuAg@CeO2NCs dispersion, 500 μL of HAc-NaAc buffer solution with pH = 3.5, 500 μL (3 mM) of TMB solution, 150 μL (100 mM) of H2O2, and 250 μL (10 mM) of AAP in sequence.

[0131] Sample 3: In a 2 mL centrifuge tube, add 30 μL (1 mg / mL) of AuAg@CeO2NCs dispersion, 500 μL of HAc-NaAc buffer solution with pH = 3.5, 500 μL (3 mM) of TMB solution, 150 μL (100 mM) of H2O2, and 250 μL (10 μg / mL) of ALP in sequence.

[0132] Sample 4: Add 30 μL (1 mg / mL) of AuAg@CeO2NCs dispersion, 500 μL of HAc-NaAc buffer solution with pH = 3.5, 500 μL (3 mM) of TMB solution, 150 μL (100 mM) of H2O2, and 250 μL of reaction solution 1 in a 2 mL centrifuge tube.

[0133] The above four samples were mixed thoroughly and then irradiated under 808nm laser (1w / cm 2 ) for 10 min, the absorption of 400-800 nm was tested using a UV-Vis-NIR spectrometer, and the samples were photographed.

[0134] The experimental results are as follows Fig.13 As shown. Under near-infrared laser irradiation, the TMB-H2O2 system is catalytically oxidized by AuAg@CeO2NCs, and the color of the system turns blue, with a significant characteristic absorption peak at 652nm; when AAP or ALP is added to the system alone, the absorption of the system does not change significantly, and the color of the sample does not become lighter; when reaction solution 1 is added to the system, the color of the system becomes significantly lighter, and its absorption value at 652nm decreases significantly. The above experimental phenomena show that ALP can effectively inhibit the oxidation of TMB in the presence of AAP, causing the system to become significantly lighter in color, thereby realizing the colorimetric detection of ALP.

[0135] Example 5. Optimization of experimental conditions

[0136] (1) Material concentration selection

[0137] In 2mL centrifuge tubes, 500μL of pH=3.5 HAc-NaAc buffer solution, 500μL (3mM) TMB solution, 150μL (100mM) H2O2 were added in sequence, and then 7.5μL, 12μL, 22.5μL, 30μL, 37.5μL (1mg / mL) of AuAg@CeO2NCs dispersion were added, and finally deionized water was added to 1.5mL to ensure that the final concentration of the material was 5μg / mL, 10μg / mL, 15μg / mL, 20μg / mL, and 25μg / mL, respectively. The above samples were mixed and then illuminated under 808nm laser (1w / cm 2 ) for 10 min, and the absorption at 652 nm was measured and recorded using a UV-visible-near infrared spectrometer. The group without material was used as a blank control.

[0138] The test results are as follows Fig.14-A shows that when the material concentration reaches above 20 μg / mL, its relative absorption value at 652 nm has reached above 0.8. In order to improve the sensitivity of the method, the optimal concentration of the material is determined to be 20 μg / mL.

[0139] (2) pH selection

[0140] In 2 mL centrifuge tubes, 30 μL (1 mg / mL) of AuAg@CeO2NCs dispersion, 500 μL (3 mM) of TMB solution, 150 μL (100 mM) of H2O2 were added in sequence, and then 500 μL of HAc-NaAc buffer solution with pH values ​​of 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, and 6.0 were added, and finally deionized water was added to 1.5 mL. The above samples were mixed and then illuminated under 808 nm laser (1 w / cm 2 ) for 10 min, and the absorption at 652 nm was measured and recorded using a UV-Vis-NIR spectrometer. The group without adding buffer solution was used as a blank control.

[0141] The test results are as follows Fig.14 -B, when the pH of the system is about 3.5, the relative absorption value at 652nm is the largest, so the optimal pH condition for the reaction of this system is determined to be 3.5.

[0142] (3) Selection of chromogenic substrate concentration

[0143] 1) TMB concentration: 30 μL (1 mg / mL) of AuAg@CeO2NCs dispersion and 500 μL of HAc-NaAc buffer solution with a pH of 3.5 were added to 2 mL centrifuge tubes, followed by 0 μL, 50 μL, 100 μL, 200 μL, 250 μL, 300 μL, 400 μL, 500 μL, 600 μL (3 mM) of TMB solution and 150 μL (100 mM) of H2O2, and finally deionized water was added to 1.5 mL. The above samples were mixed and then illuminated under 808 nm laser (1 w / cm 2 ) for 10 min, and the absorption at 652 nm was tested and recorded using a UV-Vis-NIR spectrometer.

[0144] The test results are as follows Fig.14 -C, when the TMB concentration reaches 1 mM, its relative absorbance at 652 nm reaches above 0.8, and its concentration continues to increase, and the absorption is maintained at around 0.8, so it is determined that the TMB concentration reaches 1 mM.

[0145] 2) H2O2 concentration: 30 μL (1 mg / mL) of AuAg@CeO2NCs dispersion, 500 μL of HAc-NaAc buffer solution with a pH of 3.5, and 500 μL (3 mM) of TMB solution were added to 2 mL centrifuge tubes, and then 0 μL, 1.5 μL, 4.5 μL, 7.5 μL, 15 μL, 75 μL, 150 μL, and 225 μL (100 mM) of H2O2 were added, and finally, deionized water was added to 1.5 mL. The above samples were mixed and then illuminated under 808 nm laser (1 w / cm 2 ) for 10 min, and the absorption at 652 nm was tested and recorded using a UV-Vis-NIR spectrometer.

[0146] Test results such as Fig.14 -D, when the final concentration of H2O2 reaches 10mM, its relative absorbance at 652nm reaches the maximum value, and its concentration continues to increase, and the absorption is maintained at around 0.8. Therefore, the final concentration of H2O2 is determined to be 10mM.

[0147] Example 6. Photothermal Enhancement of AuAg@CeO2NCs POD Colorimetric Detection of ALP

[0148] (1) Preparation of reaction solution for incubating ALP: 6000 μL Tris-HCl (pH=8.0), 600 μL (10 mM) L-ascorbic acid-2-phosphonate (AAP), 600 μL (10 μg / mL) ALP, and 7800 μL deionized water were respectively placed in a 15 mL centrifuge tube, mixed thoroughly, and placed in a 37°C water bath for reaction for 30 min. This was recorded as reaction solution 1.

[0149] (2) In a 2 mL centrifuge tube, add 30 μL (1 mg / mL) of AuAg@CeO2NCs dispersion, 500 μL of HAc-NaAc buffer solution with pH = 3.5, 500 μL (3 mM) of TMB solution, and 150 μL (100 mM) of H2O2 in sequence, and then add 0 μL, 25 μL, 50 μL, 75 μL, 100 μL, 125 μL, 150 μL, 175 μL, 200 μL, 225 μL, and 250 μL of reaction solution 1 respectively, and then fill up to 1500 μL with deionized water. Ensure that the final ALP concentration of each sample is 0U / L, 0.67U / L, 1.33U / L, 2.00U / L, 2.67U / L, 3.33U / L, 4.00U / L, 4.67U / L, 5.33U / L, 6.00U / L, 6.67U / L. Mix the above samples evenly and irradiate them under 808nm laser (1w / cm 2) for 10 min, and the absorption spectrum of 400-800 nm was measured by UV-visible-near infrared spectrometer and recorded. Each sample was measured three times in parallel. The test results are shown in Fig.15 As shown. 652 The standard working curve for detecting ALP is drawn with the concentration of ALP as the ordinate and the concentration of ALP as the abscissa. Fig.16 Finally, the linear equation for detecting ALP is ΔA 652 =0.0747c+0.1547(r=0.9949), and the linear range of detection is 0.67U / L-6.67U / L.

[0150] (3) The above samples were photographed, and RGB color was picked up using a smartphone colorimetric software, with R, G, and B values ​​as the ordinate and ALP concentration as the abscissa, to construct a colorimetric analysis method for detecting ALP. The color change of the reaction solution in the presence of ALP concentration is shown in the following figure. Fig.17 As shown, the RGB color values ​​of the reaction solution in the presence of different concentrations of ALP are as follows Fig.18 As shown, the standard working curve of colorimetric detection of ALP is as follows Fig.19 As shown, the linear equation for detecting ALP is ΔV R =10.2304c+27.3758, r=0.9899, ​​where ΔV R It represents the relative value of R, that is, the difference between the system R value when the system ALP concentration is 0 and the R value when a certain ALP concentration is added to the system. c represents the ALP concentration. The linear range of detection is 1.33-6.67U / L.

[0151] The present invention uses colorimetry to detect actual samples, mainly based on the addition of different concentrations of ALP standard solutions, the color of the system gradually becomes lighter. The standard working curve established according to the changes in the RGB values ​​of the sample colors corresponding to different concentrations of ALP is used for determination. The RGB value of the actual sample is substituted into the standard working curve for calculation to obtain the corresponding ALP concentration. The RGB value determination method of the sample to be tested is as follows:

[0152] 1) Pretreatment: Take an actual sample of unknown ALP concentration, remove insoluble impurities by centrifugation, and dilute to a suitable multiple to obtain a sample solution to be tested; wherein the centrifugal speed is 15000 rpm, the centrifugal time is 15 min, and the dilution multiple is gradually diluted to 1000 times of the original solution.

[0153] 2) The sample solution obtained in step 1) was incubated with AAP at 37°C; then added to the detection system containing AuAg@CeO2NCs-TMB-H2O2 for detection (30μL AuAg@CeO2NCs dispersion, 500μL HAc-NaAc buffer solution with pH=3.5, 500μL TMB solution, 150μL H2O2, 250μL sample solution, and finally filled with deionized water to 1.5mL); and irradiated with 808nm laser for 10 minutes at a power density of 1w / cm 2 , UV-visible-near infrared spectrometer was used to test the absorption value of the sample at 652nm;

[0154] 3) Take a photo of the sample, use the mobile phone color picking software to pick the color, and substitute the corresponding R value into the established equation (ΔV R =10.2304c+27.3758), the ALP concentration can be calculated.

[0155] Example 7. Selectivity and anti-interference ability test:

[0156] (1) Selectivity: Add 30 μL (1 mg / mL) of AuAg@CeO2 NCs dispersion, 500 μL of pH 3.5 HAc-NaAc buffer solution, 500 μL (3 mM) TMB solution, 150 μL (100 mM) H2O2, 250 μL of reaction solution, or some common inorganic ions, amino acids, starch and sugars, etc., to a 2 mL centrifuge tube, and finally add deionized water to 1.5 mL. Mix well and illuminate under 808 nm laser (1 w / cm 2 ) for 10 min, and the absorption value at 652 nm was tested and recorded using a UV-Vis-NIR spectrometer.

[0157] (2) Anti-interference: Add 30 μL (1 mg / mL) of AuAg@CeO2 NCs dispersion, 500 μL of pH=3.5 HAc-NaAc buffer solution, 500 μL (3 mM) TMB solution, 150 μL (100 mM) H2O2, 250 μL of reaction solution, and some common inorganic ions, amino acids, starch and sugars, etc., and finally add deionized water to 1.5 mL. Mix well and illuminate under 808 nm laser (1 w / cm 2 ) for 10 min, and the absorption value at 652 nm was tested and recorded using a UV-Vis-NIR spectrometer.

[0158] The selectivity and anti-interference ability of the method for detecting ALP are judged by the influence of each interfering substance in the system on the absorption of the system at 652nm. The test results of selectivity and anti-interference ability are as follows: Fig. 20 -A and Fig. 20 -B, the interferences have good selectivity for the detection of ALP by this method, and the anti-interference ability is also strong. The results show that this method can be applied to the detection of ALP content in actual samples.

[0159] Example 8. Determination of ALP content in actual samples

[0160] This example adopts the standard addition method, using serum and urine samples as actual samples, and measuring the spiked recovery of ALP in actual samples within the linear range to verify whether the method is reliable. The specific method is as follows:

[0161] (1) Serum and urine samples were pretreated by centrifugation (15000 rpm for 15 min) and dilution (gradually diluted to 1000 times the original solution).

[0162] (2) Serum: 30 μL (1 mg / mL) of AuAg@CeO2 NCs dispersion, 500 μL of HAc-NaAc buffer solution with pH = 3.5, 500 μL (3 mM) of TMB solution, 150 μL (100 mM) of H2O2, 250 μL of reaction solution containing ALP (i.e., reaction solution 1 in Example 6) were added to a 2 mL centrifuge tube in sequence. At the same time, 250 μL of serum diluted 1000 times was added, and finally, deionized water was added to make up to 1.5 mL. The final concentrations of the ALP standard solutions were 4 U / L, 5.33 U / L, and 6.0 U / L, respectively. The above samples were mixed evenly and irradiated under 808 nm laser (1 w / cm 2 ) for 10 min, and the absorbance at 652 nm was measured by UV-visible-near infrared spectrometer and recorded. Each sample was measured three times in parallel. Then the spiked recovery was calculated respectively.

[0163] (3) Urine sample: 30 μL (1 mg / mL) of AuAg@CeO2 NCs dispersion, 500 μL of pH=3.5 HAc-NaAc buffer solution, 500 μL (3 mM) of TMB solution, 150 μL (100 mM) of H2O2, 250 μL of reaction solution containing ALP (i.e., reaction solution 1 in Example 6) were added to a 2 mL centrifuge tube in sequence. At the same time, 250 μL of urine sample diluted 1000 times was added, and finally, deionized water was added to 1.5 mL. The final concentrations of the ALP standard solutions were 4 U / L, 5.33 U / L, and 6.0 U / L, respectively. The above samples were mixed evenly and irradiated under 808 nm laser (1 w / cm 2 ) for 10 min, and the absorbance at 652 nm was measured by UV-visible-near infrared spectrometer and recorded. Each sample was measured three times in parallel. Then the spiked recovery was calculated respectively.

[0164] The test results are shown in Table 1. The data show that the recovery rate of ALP in serum and urine samples is 94.8%-105.4%, indicating that this method can be used to determine the ALP content in actual samples.

[0165] Table 1. Test results of spiked recovery of ALP in human serum and urine samples

[0166]

Claims

1. A method for preparing AuAg@CeO2 nanocages using a two-step hydrothermal method, characterized in that: The steps include: (1) mixing HAuCl4, CTAB, and NaBH4 solutions in sequence to obtain reaction solution A; (2) mixing HAuCl4, CTAC, and ascorbic acid solution in sequence to obtain reaction solution B; (3) adding the reaction solution A obtained in step (1) to the reaction solution B obtained in step (2) to obtain a quasi-spherical Au nanoseed dispersion; (4) mixing DTAC, AA, AgNO3 and the Au nanoseed dispersion obtained in step (3), and reacting in a water bath to obtain Au@Ag core-shell nanocubes; (5) adding HAuCl4 solution to the Au@Ag core-shell nanocubes obtained in step (4) to continue the reaction to obtain a AuAg nanocage dispersion; (6) Add CTAB and K2PtCl6 to the AuAg nanocage dispersion obtained in step (5) in sequence and vortex; then add Ce(AC)3 and react to obtain AuAg@CeO2 nanocage dispersion.

2. The method according to claim 1, characterized in that In step (1), the volume ratio of the HAuCl4, the CTAB, and the NaBH4 solution is 4-6:4-6:0.5-0.7; and / or in step (2), the volume ratio of the HAuCl4, the CTAC, and the ascorbic acid solution is 3-5:3-5:2-4; and / or in step (3), the volume ratio of the reaction solution A to the reaction solution B is 0.04-0.06:8-15; and / or in step (4), the DTAC, the AA, the AgNO 3 and the Au nanoseed dispersion is 2-5:0.4-0.6:0.4-0.6:0.01-0.03; and / or in step (5), the volume ratio of the Au@Ag core-shell nanocubes and the HAuCl4 solution is 3.5-4.5:1-2; and / or in step (6), the volume ratio of the AuAg nanocage dispersion, the CTAB, the K2PtCl6, and the Ce(AC)3 is 15-20:15-20:4-10:4-10.

3. The method according to claim 1, characterized in that In step (4), the reaction conditions are 80-100° C. in a water bath for 5-10 hours.

4. The method according to claim 1, characterized in that In step (6), the reaction conditions are 90-120° C. for 50 min-2 h.

5. AuAg@CeO2 nanocage prepared by the method described in any one of claims 1 to 4.

6. The method for detecting ALP content using the AuAg@CeO2 nanocage according to claim 5, characterized in that: The steps include: A. preparing a reaction solution for incubating ALP: mixing Tris-HCl, L-ascorbic acid-2-phosphonate, ALP and deionized water, and reacting to obtain a reaction solution 1; B. Take different volumes of the reaction solution 1, mix with the AuAg@CeO2 nanocage dispersion, HAc-NaAc buffer solution, TMB solution, H2O2 and ionized water to obtain a series of standard working solutions; irradiate the series of standard working solutions under laser, and then use UV-visible-near infrared spectrometer to test its absorption intensity at 400-800nm; and use ΔA 652 The vertical axis is the ordinate, the concentration of ALP is the horizontal axis, and the standard working curve is established; C. By using RGB color picking, with R, G, B values ​​as the ordinate and ALP concentration as the abscissa, a colorimetric analysis method for detecting ALP was established to obtain a standard working curve for colorimetric detection of ALP; D. Detect the RGB value of the sample to be tested, substitute it into the standard working curve obtained in step C, and obtain the ALP concentration of the sample to be tested.

7. The method according to claim 6, characterized in that In step B, the final concentration of ALP in the series of standard working solutions is 0 U / L, 0.67 U / L, 1.33 U / L, 2.00 U / L, 2.67 U / L, 3.33 U / L, 4.00 U / L, 4.67 U / L, 5.33 U / L, 6.00 U / L, and 6.67 U / L.

8. The method according to claim 6, characterized in that In step B, the final concentration of the AuAg@CeO2 nanocage dispersion is 18-25 μg / mL; the pH of the HAc-NaAc buffer solution is 3.0-4; the final concentration of the TMB solution is 0.9-1.2 mM; and the final concentration of the H2O2 is 6-15 mM.

9. The method according to claim 6, characterized in that In step C, the linear equation for colorimetric detection of ALP is ΔV R =10.2304c+27.3758, where ΔV R represents the relative value of R, c represents the ALP concentration, and its linear range of detection is 1.33-6.67U / L.

10. The method according to claim 6, characterized in that The samples to be tested include serum and urine samples.

Citation Information

Patent Citations

  • Preparation method and application of electrochemical biosensor based on gold nanocage

    CN108344788A

  • Au-CeO2 photocatalysis-photothermal composite material, preparation method and application thereof

    CN113828769A

  • Colorimetric / photo-thermal dual-mode detection method for alkaline phosphatase and butyrylcholine esterase

    CN117388184A

  • Preparation method of AuAg-CeO2 bimetallic supported photocatalyst

    CN117772195A

  • Rod-like multi-metal nano-enzyme with burr structure as well as preparation method and application of rod-like multi-metal nano-enzyme

    CN118437936A